Axillary Artery Dissection and Thrombosis after Closed Proximal Humerus Fracture – a Rare Interdisciplinary Challenge - Razaeian, Sam; Rustum, Saad; Sonnow, Lena; Meller, Rupert; Krettek, Christian; Hawi, Nael (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background Proximal humerus fractures account for 4 – 6% of all fractures and are a common result of low-energy trauma in the elderly. Concomitant neurovascular injury of the neighboring axillary artery and brachial plexus is a rarity, but has enormous impact on therapy, rehabilitation and prognosis. Diagnosis of axillary artery injury may be delayed due to its varied clinical presentation and lead to prolonged ischemia, distal necrosis and even loss of limb. Thorough clinical examination, high suspicion and identification of known predictors can be helpful in early diagnosis of this rare injury.Patients/Material and Methods We report a case of an intoxicated 76-year-old male who sustained a dislocated proximal humerus fracture, resulting in concomitant brachial plexopathy and axillary artery dissection with secondary thrombosis after a low-energy fall from standing height. Due to mistriage as a neurological emergency the somnolent patient presented under delayed circumstances at our traumatological emergency department, demonstrating pain, paleness, paralysis, paresthesia and non-palpable wrist pulses. Diagnosis was made through high suspicion after clinical examination with the aid of CT angiography. Emergent open reduction and anatomic shoulder hemiarthroplasty was performed followed by axillobrachial interposition grafting using a reversed saphenous vein graft and brachial plexus exploration.Results The surgical treatments were uncomplicated. The affected limb remains viable at 6-week follow-up; however, active shoulder function is limited due to residual brachial plexopathy.Conclusion Despite early diagnosis and management of this rare injury, the prognosis for functional recovery is guarded and largely dictated by the extent of neurological injury in the setting of concomitant brachial plexopathy. Brachial plexopathy is highly associated with axillary artery injury and its impact often underestimated in comparison due to its non-limb-threatening nature in the acute setting. Future studies should focus on the long-term prognosis for functional recovery in patients with this rare injury pattern.Hintergrund Neurovaskuläre Begleitverletzungen der unmittelbar benachbarten A. axillaris sowie des Plexus brachialis sind im Rahmen proximaler Humerusfrakturen mit einer Prävalenz von 0,09 bzw. 0,14% eine Rarität, haben jedoch erhebliche Auswirkungen auf die Wahl der Therapie und Prognose. Begleitende Verletzungen der A. axillaris können sich klinisch sehr heterogen präsentieren und, dem ausgeprägten Kollateralnetzwerk der Schulter geschuldet, auch maskiert bleiben, was ihre Diagnose in der Akutsituation erschwert und undiagnostiziert bei prolongierter Ischämie zu Nekrosen bis zum Verlust der Extremität führen kann.Patienten/Material und Methoden Wir berichten im Folgenden über Diagnose, Therapie und das funktionelle Ergebnis nach erlittener, traumatischer Dissektion und Thrombosierung der A. axillaris sowie Plexusaffektion im Rahmen einer geschlossenen, proximalen Humerusfraktur bei einem 76-jährigen Patienten, der mit erheblicher Verzögerung nach Fehltriagierung über die Neurologie in der unfallchirurgischen Notaufnahme vorstellig wurde.Ergebnisse Sechs Wochen postoperativ ist trotz klinisch-radiologisch adäquatem Versorgungsergebnis das funktionelle Outcome unter persistierender Plexopathie bei einer subjektiven Schulterfunktion von nur 10% und einem Constant-Shoulder-Score von 17/100 Punkten limitiert.Schlussfolgerung Trotz früher Diagnose und Therapie ist das Outcome durch das Maß der neurologischen Morbidität bei begleitender Plexusaffektion bestimmt und limitiert, die weder akut lebens- noch extremitätengefährdend ist und deshalb in ihrer Bedeutung oft unterschätzt wird. Die Langzeitprognose von Patienten mit diesem Verletzungsmuster bleibt ungewiss.
Keywords: proximal humerus fracture; axillary artery; brachial plexus; dissection; thrombosis